Public perception on the amendment of mandatory death penalty against drug offenders in Malaysia: drug trafficking / Nuralya Nabilah Mohamad Sapiny - Mohamad Sapiny, Nuralya Nabilah (2018)
This chapter generally focus on the background of the study on public opinion on the amendment of mandatory death penalty against drug offenders in Malaysia which specifically about drug trafficking. The background of the study will be discussed in Section 1.1 while followed by Section 1.2 which explained on the problem statement of the study. Section 1.3 stated the research questions and research objectives stated in the Section 1.4. In addition, the information on the scope of study explained by Section 1.5 and on the hand Section 1.6 explained on the significant of doing this study. Lastly, Section 1.7 is about the terms and concepts used in this study.